Commitment to inclusion: a review of SEND provision across mainstream secondary schools in Southampton. Issue 1 (24th January 2021) - Belli, Clare
Abstract : This short piece of action research seeks to identify the strengths of secondary school provision for students with SEND, in order to provide a city wide overview in which good practice and expertise can be shared. It also considers the particular barriers faced by secondary schools and examines how schools are working to overcome these barriers. The research suggests that despite the challenges of reduced funding, some schools are developing innovative ways to maximise resources and provide flexible pathways of provision for pupils with SEND. These include establishing a graduated approach to support with clear mechanisms for early identification of need, ongoing monitoring of progress and robust systems for self‐evaluation leading to school improvement. In addition, some schools have sought to design a modified and enhanced curriculum for more vulnerable students, with flexible access to short‐term interventions and alternative provision. However, there is evidence to suggest that an emphasis on summative attainment data with a lack of specificity around target setting, sometimes leaves pupils unclear about the progress they are making and what they need to do to improve. The research suggests that schools should consider how a vision for SEND needs to be driven by senior leadership teams and how the role of the SENCo can be strengthened by adopting the principles of distributed leadership to bring about collective influence. Consideration of how schools can work together to share expertise and develop structured opportunities for continuous professional development, could help to secure positive outcomes for pupils with SEND and create long‐term sustainability.